2017
DOI: 10.1186/s13014-017-0884-y
|View full text |Cite
|
Sign up to set email alerts
|

Nadir PSA is a strong predictor of treatment outcome in intermediate and high risk localized prostate cancer patients treated by definitive external beam radiotherapy and androgen deprivation

Abstract: BackgroundThe aim of this study is to investigate the effect of tumor characteristics and parameters of treatment response in predicting biochemical disease-free survival (BFS) for patients with intermediate or high risk prostate cancer treated by combined definitive external beam radiation therapy (EBRT) and androgen deprivation therapy (ADT).MethodsBetween June 1995 and January 2015, 375 patients with localized prostate cancer and a National Comprehensive Cancer Network (NCCN) intermediate or high risk categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 26 publications
0
25
1
1
Order By: Relevance
“…The prognostic significance of patients’ age as an independent predictor of biochemical recurrence is still controversial. Some reports recognized advanced age as an indicator of poorer biochemical outcome [70], while others did not find any association in patients undergoing radical prostatectomy [71] or radiotherapy [72]. However, another study suggested that in high-risk younger patients, biochemical recurrence-free survival is poorer than in older patients [73].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of patients’ age as an independent predictor of biochemical recurrence is still controversial. Some reports recognized advanced age as an indicator of poorer biochemical outcome [70], while others did not find any association in patients undergoing radical prostatectomy [71] or radiotherapy [72]. However, another study suggested that in high-risk younger patients, biochemical recurrence-free survival is poorer than in older patients [73].…”
Section: Discussionmentioning
confidence: 99%
“…Investigators from The American University of Beirut Medical Center (AUBMC) have shown that nadir PSA at 0.06 ng/ml is a strong predictor of outcome in a cohort of patients with intermediate and high-risk localized prostate cancer [28].…”
Section: Definitive Radiation Therapy For High-risk and Locally Advanmentioning
confidence: 99%
“…A-ADT for more than 12 months after RT was associated with nadir PSA <0.2 ng/mL significantly more frequently than ADT for less than 12 months in high-risk patients (88% in A-ADT ≥12 months vs. 74% in A-ADT <12 months, p < 0.0001) [ 17 ]. It has been reported that a nadir PSA level of <0.06 ng/mL is a powerful prognostic factor for 5-year BCFFS for intermediate- and high-risk patients treated with RT and long-term A-ADT (96% vs. 74%, p < 0.001) [ 18 ]. Similarly, a nadir PSA value of <0.001 ng/mL affected 5-year BCFFS (99% vs. 82.8%, p < 0.001) in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…that a nadir PSA level of <0.06 ng/mL is a powerful prognostic factor for 5-year BCFFS for intermediate-and high-risk patients treated with RT and long-term A-ADT (96% vs. 74%, p < 0.001) [18]. Similarly, a nadir PSA value of <0.001 ng/mL affected 5-year BCFFS (99% vs. 82.8%, p < 0.001) in the current study.…”
Section: Plos Onementioning
confidence: 95%